The sonata - Schmidt, Thomas (Musicologist) (Cambridge, UK ; New York : Cambridge University Press, 2011)
What is a sonata? Literally translated, it simply means"'instrumental piece." It is the epitome of instrumental music, and is certainly the oldest and most enduring form of "pure" and independent instrumental composition, beginning around 1600 and lasting to the present day. Schmidt-Beste analyses key aspects of the genre including form, scoring and its social context--who composed, played and listened to sonatas? In giving a comprehensive overview of all forms of music which were called "sonatas" at some point in musical history, this book is more about change than about consistency--an ensemble sonata by Gabrieli appears to share little with a Beethoven sonata, or a trio sonata by Corelli with one of Boulez's piano sonatas, apart from the generic designation. However, common features do emerge, and the look across the centuries--never before addressed in a single-volume survey--opens up new and significant perspectives [Publisher description].
Chapter 1 : Definitions. Sonata and canzona ; Sonata and sinfonia ; Sonata and concerto ; Sonata and suite/partita ; The sonata and free instrumental genres : toccata, ricercar, capriccio. fantasia -- Chapter 2 : Form. The "free" sonata in the seventeenth century ; Corelli and his legacy ; Sonata cycles and "sonata form" after 1750 ; Beethoven's sonatas : consummating or transcending Classical form? ; The cycle ; The sonata after Beethoven ; Sonata composition in the twentieth century -- Chapter 3 : Functions and aesthetics. Locations and occasions ; Target groups : professionals, connoisseurs and amateurs ; Learned style ; Virtuosity ; Sonata form as an aesthetic paradigm ; Absolute music? On meaning and programmaticism -- Chapter 4 : Scoring and texture. Developments in the seventeenth and eighteenth centuries ; The paradigm shift of ca. 1750 ; The age of the piano sonata ; Piano and others ; The sonata for unaccompanied solo instrument ; The organ sonata.
Includes bibliographical references (pages 243-249) and index.
Translated from the German.
Keywords: Sonata; Sonata form; Sonata; Sonata form; Sonate; Geschichte; Lehrbuch